GENDER EDUCATION OF PRESCHOOL CHILDREN: THEORETICAL AND PRACTICAL ASPECTS - Machynska, Nataliіa (Continuing Professional Education: Theory and Practice, 2024)
The article analyzes regulatory documents and theoretical and methodological research by Ukrainian scientists on the problem of gender education and gender upbringing of preschool children. The author revealed the topic of gender and the gender approach, which is a leading focus in the national system of preschool education. The article demonstrates that gender issues are interdisciplinary, forming the subject of scientific investigations in sociology, cultural studies, history, philology, psychology, and pedagogy. It is noted that gender is a complex concept used in several meanings (gender as social-role and cultural interpretation of personal traits and behavior patterns of men and women; acquisition of sociality by individuals; policy of equal rights and opportunities for men and women, etc.). Based on the analysis of scientific research, it is emphasized that the gender approach in preschool education is an individual approach to the manifestation of a preschool child’s identity. It is proven that this approach creates personal conditions for freedom of choice, provides opportunities for self-realization, helps to be sufficiently flexible, and gives the ability to use various behavioral opportunities in the socio-cultural environment. The article proposes and characterizes the rules for organizing and structuring the content of ethical discussions with preschool children regarding the understanding of gender education (information should be age-appropriate and meet children’s needs; the teacher should reflect their own attitude towards the topic of discussion; questions arising during the discussion should be answered, etc.). The article provides advice and recommendations for educators of preschool institutions and parents to effectively organize gender education in preschool institutions and families (establishing close cooperation in the context of pedagogical interaction between educator and psychologist, educator and family; thorough study of individual characteristics of preschool children, etc.).